Naturalism: Metaphysics, Mandate, or Myth? - Rozema, David (Theology today, 2018)
In May of 1947, C. S. Lewis's book Miracles was published, the third chapter of which was entitled, "The Self-contradiction of Naturalism." In this chapter, Lewis presented a reductio argument, concluding that the metaphysical theory of Naturalism, if assumed to be true, undermines itself. Lewis's main aim in giving this argument against naturalism is to leave us with the only alternative to naturalism: supernaturalism. This argument for the existence of the supernatural (i.e., God) has come to be known as "the Argument from Reason." It has become a staple argument among present-day Christian apologists. Rather than offering either a defense or a refutation of the argument, in this article I wish to do a preliminary examination of what those who argue about naturalism might mean by the term. The aim of such an examination is to determine if the debates over naturalism can even get off the ground. I use the 1948 "debate" between C. S. Lewis and Elizabeth Anscombe, along with a little-known paper ("Naturalism") by the American philosopher O. K. Bouwsma, to show how the arguments dissolve upon grammatical investigation, and a more sensible understanding of the naturalist "hypothesis" is to take it as a mandate. Finally, I take up a third possible interpretation of naturalism, suggested by Lewis himself, that its appeal is strongest when it is couched in mythical terms.